Pemanfaatan Fitur Google untuk Mendukung e-Government di Tingkat Desa/Kelurahan - Irmawati Sagala; Yudi Armansyah; Nailil Husna; Wenny Dastina (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Although the implementation of e-government in the government system in Indonesia has been running for almost decades, in practice, there are still many local government units, mainly villages and sub-districts, that encounter technical problems. The main obstacle faced by the village/sub-district government is the capacity of human resources and the availability of budgeting to support the use of information systems. Based on this issue, the Government Science Department, in collaboration with the Community Service Program (KKN) of UIN Sulthan Thaha Saifuddin Jambi students in 2021, held the e-government workshop for villages/sub-districts governments in Jambi Province with the theme "Utilizing Google Features to Support the Implementation of e-Government at the Village/sub-district Level." The organizer considered these features can overcome the problems of limited budget and human resource capacity because Google's features, apart from being accessible for free, are also quite familiar, especially since the Covid-19 pandemic. The introductory workshop takes about four hours, with offers of further assistance for villages/sub-district who will establish an advanced program. During August-September 2021, the workshop was held in six villages/sub-district spread over three regencies, namely Tanjung Jabung Timur (one village), Muaro Jambi (two villages), and Batanghari (two villages and one sub-district). In this workshop, village/sub-district officials are directly guided to create several online administrative services.